Influence of the phosphoenolpyruvate:carbohydrate phosphotransferase system on toxin gene expression and virulence in Bacillus anthracis - Bier, Naomi; Hammerstrom, Troy G.; Koehler, Theresa M. (Molecular microbiology, 2020)
Summary AtxA, the master virulence gene regulator of Bacillus anthracis, is a PRD‐Containing Virulence Regulator (PCVR) as indicated by the crystal structure, post‐translational modifications and activity of the protein. PCVRs are transcriptional regulators, named for PTS Regulatory Domains (PRDs) subject to phosphorylation by the phosphoenolpyruvate phosphotransferase system (PEP‐PTS) and for their impact on virulence gene expression. Here we present data from experiments employing physiological, genetic and biochemical approaches that support a model in which the PTS proteins HPr and Enzyme I (EI) are required for transcription of the atxA gene, rather than phosphorylation of AtxA. We show that atxA transcription is reduced 2.5‐fold in a mutant lacking HPr and EI, and that this change is sufficient to affect anthrax toxin production. Mutants harboring HPr proteins altered for phosphotransfer activity were unable to restore atxA transcription to parent levels, suggesting that phosphotransfer activity of HPr and EI is important for regulation of atxA. In a mouse model for anthrax, a HPr– EI– mutant was attenuated for virulence. Virulence was restored by expressing atxA from an alternative, PTS‐independent, promoter. Our data support a model in which HPr transfers a phosphate to an unidentified downstream transcriptional regulator to influence atxA gene transcription. AtxA is a critical virulence gene regulator of Bacillus anthracis. The crystal structure, post‐translational modifications and activity of AtxA suggest that the protein is phosphorylated by the phosphoenolpyruvate phosphotransferase system (PEP‐PTS). We present data from physiological, genetic and biochemical approaches supporting a model in which the PTS proteins Hpr and EI are required for transcription of the atxA gene, rather than phosphorylation of AtxA, and that at PTS mutant is attenuated for virulence.